Infrastructure Sharing as an Opportunity to Promote Competition in Local Access Networks - João Paulo Pereira; Pedro Ferreira (Journal of Computer Networks and Communications)
Telecom infrastructures are facing unprecedented challenges, with increasing demands on network capacity. Today, network operators must determine how to expand the existing access network infrastructure into networks capable of satisfying the user’s requirements. Thus, in this context, providers need to identify the technological solutions that enable them to profitably serve customers and support future needs. However, the identification of the “best” solution is a difficult task. Although the cost of bandwidth in the active layer has reduced significantly (and continually) in recent years, the cost of the civil works—such as digging and trenching—represents a major barrier for operators to deploy NGA infrastructure. Duct is a critical part of the next-generation access networks, and its sharing would reduce or eliminate this capital cost and this barrier to entry. The aim of this paper is to provide a better understanding of the economics of broadband access networks technologies (wireline and wireless), their role in the deployment of several services in different regions, and the development of competition in the access networks.